2019
DOI: 10.36348/sjeat.2019.v04i10.002
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Symmetric Data Encryption Algorithms: AES and Blowfish

Abstract: People are transferring large amount of data that are critical and consume large amount of time through the Internet such as email, banking transaction and online purchase. But due to high exposure they are susceptible to being heavily attacked or become attractive targets for attackers. This can be solved by using a modern phenomenon called symmetric encryption. Symmetric encryption is used to ensure that information is hidden from anyone for whom it is not intended. This research conducted a performance eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Tiwari et al [21] examined the suitability of AES and RSA algorithms and noticed that they offered a high level of encryption capacity because they depend on public and private keys shared securely to reduce the risk of unauthorized viewing or modification of documents and messages. Buhari et al [24] investigated the capabilities of AES and Blowfish and found that the two algorithms offer benefits such as low execution times that can enhance user experience. Yousif [26] argued that the implementation of a public and private key helps encryption by reducing the risk of individuals having both keys and modifying messages and documents.…”
Section: Discussion Of Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Tiwari et al [21] examined the suitability of AES and RSA algorithms and noticed that they offered a high level of encryption capacity because they depend on public and private keys shared securely to reduce the risk of unauthorized viewing or modification of documents and messages. Buhari et al [24] investigated the capabilities of AES and Blowfish and found that the two algorithms offer benefits such as low execution times that can enhance user experience. Yousif [26] argued that the implementation of a public and private key helps encryption by reducing the risk of individuals having both keys and modifying messages and documents.…”
Section: Discussion Of Related Workmentioning
confidence: 99%
“…10 Buhari et al [24] AES and Blowfish Blowfish is more efficient compared with AES when handling most file types. Therefore, Blowfish outperforms AES in most of the test cases.…”
Section: Discussion Of Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Denial-of-Service (DoS) and Distributed Denial-of-Service (DDoS) are common attacks against availability. While virtual systems are the common techniques to keep availability [28]. Performance: Besides security requirements, it is important to refer to the most common requirement to implement and evaluate any authentication system performance.…”
Section: B Security Requirements and Attacksmentioning
confidence: 99%
“…Based on their study, parallel AES performance increases with the increase in processors from 2 to 16. Buhari et al [22] performed a performance analysis of two symmetric encryption algorithms, Advanced Encryption Standard (AES) and Blowfish, for various data types: image, video, audio, and text. They evaluated the performance in terms of encryption time and throughput.…”
Section: Literature Reviewmentioning
confidence: 99%